Evaluation of labelling mechanisms and analytical procedures for Ga-68 labelled peptides used in positron emission tomography - Rohwer, Egmont Richard (University of Pretoria, 2023)
Thesis (PhD (Chemistry))--University of Pretoria, 2023.